DESAIN RUMAH HEINZ FRICK YANG RAMAH LINGKUNGAN DAN TERJANGKAU (Heinz Frick's House Design that is Environmentally Friendly and Affordable) - Gunawan Tanuwidjaja; Lo Leonardo Agung Mulyono; Devi Calista Silvanus (Tesa Arsitektur, 2013)
ABSTRACT The house design made by Dr.Heinz Frick, Semarang, had design features that were environmentally friendly and affordable. Firstly, the house used local labor as well as local materials beside secondhand building materials and environmentally friendly materials. Secondly, it was very functionally designed by having adequate space size, attractive scenery and adequate lighting. Thirdly, the house was built to create public awareness about sustainable design although it had not entirely been successful because of the economic and social barriers Indonesian people. Fourthly, preservation of cultural diversity was verily considered by Dr. Frick, especially Javanese culture having the concepts of the pavilion, joglo (Javanese traditional building design), and implementation of the terrace as a dining room and as a room for social interaction with the local community. Fifthly, strategy of maximizing cross air circulation and of reducing the moisture was applied in the design of the house. This was done by an open design using nako glass windows, ventilation holes, and jalousie doors that were fitted with wire gauze. Finally, water saving strategy was also applied in the house design. This was done by using rainwater for any use but not for drinking. Meanwhile, water from the Regional Water Company (PDAM) was used for drinking and cooking. It could be concluded that Dr. Heinz Frick's house design was to be a proper solution for Indonesia because of its appropriate and affordable design. Keywords: house design, environmentally friendly, affordable. ABSTRAK Desain Rumah karya Dr. Heinz Frick, Semarang, memiliki fitur - fitur desain yang ramah lingkungan sekaligus tetap terjangkau. Hal ini dimulai dengan menggunakan tenaga lokal dan material lokal, material bangunan bekas, dan material ramah lingkungan. Kedua, rumah ini didesain secara sangat fungsional dengan ukuran ruang yang memadai, pemandangan yang menarik serta pencahayaan yang memadai. Ketiga, rumah ini dibangun untul menciptakan tentang kesadaran masyarakat untuk desain berkelanjutan, walaupun belum berhasil sepenuhnya karena hambatan ekonomi dan sosial masyarakat Indonesia. Keempat, pelestarian keragaman budaya sangat diperhatikan oleh Dr. Frick, terutama budaya Jawa yang memiliki kansep pendapo, jagla, dan diterapkannya teras sebagai ruann makan dan interaksi sosial dengan komunitas setempat. Kelima, Strategi memaksimalkan sirkulasi udara silang dan mengurangi kelembabafl diterapkan dalam desain rumah ini. Hal ini dilakukan dengan desain bukaan dengan dijumpainya jendela nako, lubang ventilasi, dan pintu jalusi yang dilengkapi dengan kawat kasa. Terakhir, strategi penghematan air diterapkan juga dalam desain rumah ini. Hal ini dilakukan dengan pemanfaatan air hujan untuk penggunaan air yang tidak diminum. Sementara, air dari Perusahaan Daerah Air Minum (PDAM) penggunaan air yang tidak diminum. Sementara, air dari Perusahaan Daerah Air Minum (PDAM) masih digunakan untuk minum dan memasak. Dapat disimpulkan bahwa desain rumah Dr. Heinz Frick ini merupakan solusi yang tepat untuk Indonesia karena desainnya yang tepat guna dan terjangkau. Kata Kunci : desain rumah, ramah lingkungan, terjangkau